Implementation of a heat alert system for clinical staff in an ambulatory setting: A pilot project - Paul F Dellaripa; Candace Feldman; Lydia Gedmintas; Susan Ritter; Caleb Dresser (The Journal of Climate Change and Health)
Introduction: Climate change leads to an increasing risk of heat exposure and pre-emptive alerting to patients may be an important intervention to limit health risks related to heat. The process of providing counseling and resources related to impending dangerous heat in an ambulatory clinic setting has not been described. In this pilot project utilizing an electronic heat alert system, we describe the implementation of a clinic-level protocol for providing alert-based heat health information and proactively educating rheumatology patients in an ambulatory setting on dangerous heat conditions. Methods: Physicians, nurses and medical assistants received electronic notifications of dangerous heat forecasts via a external heat alert system (Realtime Climate Heat Risk). Participating staff completed surveys at the midpoint and end of the heat season. The primary endpoint was a self-reported estimate of the percentage of patients engaged regarding heat safety on days where heat alerts were issued. Results: There were 4 heat alert days during the study period. Half of participating staff members reported they had engaged 50 % or more of their patients on this topic. Self-reported levels of engagement by medical assistants were significantly higher than those of physicians and nurses, (W = 4.5, p-value = 0.036). Conclusions: Heat and other environmental exposures present risks to patients as the effects of climate change worsen. Heat alerts may help staff address health risks with their patients. This pilot study demonstrates that an external heat alert system can be implemented utilizing providers of different skill levels and at all points of patient interaction in an ambulatory clinic setting.